Enzymes as Green Catalysts for Precision Macromolecular Synthesis - Shoda, Shin-ichiro; Uyama, Hiroshi; Kadokawa, Jun-ichi; Kimura, Shunsaku; Kobayashi, Shiro (Chemical reviews, 2016)
The present article comprehensively reviews the macromolecular synthesis using enzymes as catalysts. Among the six main classes of enzymes, the three classes, oxidoreductases, transferases, and hydrolases, have been employed as catalysts for the in vitro macromolecular synthesis and modification reactions. Appropriate design of reaction including monomer and enzyme catalyst produces macromolecules with precisely controlled structure, similarly as in vivo enzymatic reactions. The reaction controls the product structure with respect to substrate selectivity, chemo-selectivity, regio-selectivity, stereoselectivity, and choro-selectivity. Oxidoreductases catalyze various oxidation polymerizations of aromatic compounds as well as vinyl polymerizations. Transferases are effective catalysts for producing polysaccharide having a variety of structure and polyesters. Hydrolases catalyzing the bond-cleaving of macromolecules in vivo, catalyze the reverse reaction for bond forming in vitro to give various polysaccharides and functionalized polyesters. The enzymatic polymerizations allowed the first in vitro synthesis of natural polysaccharides having complicated structures like cellulose, amylose, xylan, chitin, hyaluronan, and chondroitin. These polymerizations are "green" with several respects; nontoxicity of enzyme, high catalyst efficiency, selective reactions under mild conditions using green solvents and renewable starting materials, and producing minimal byproducts. Thus, the enzymatic polymerization is desirable for the environment and contributes to "green polymer chemistry" for maintaining sustainable society.